A randomized controlled trial on the efficacy and safety of vitamin A supplementation in children with sepsis - Fu, Qinyi; Liu, Maoxia; Zhang, Xuepeng; Fu, Jianlei; Zhang, Geng; Ji, Yi; Chen, Siyuan (Frontiers in Pediatrics, 2025)
BackgroundOur previous research confirmed that vitamin A (VA) deficiency commonly occurs in children with sepsis, and serum VA levels negatively correlate with disease severity. This study aimed to evaluate the efficacy and safety of VA supplementation (VAS) in children with sepsis.MethodsA randomized, single-blind, single-center trial was conducted from June 2020 to March 2024 involving children diagnosed with sepsis. Participants were randomly allocated to either the VAS group or the placebo group. The primary outcome was length of stay in the ICU, and secondary outcomes included hospital length of stay, 28-day mortality, duration of mechanical ventilation, and antibiotic usage. Vital signs, clinical symptoms, and laboratory data were recorded, and statistical analyses assessed the efficacy and safety of VAS.ResultsA total of 156 children with sepsis were enrolled: 72 in the VAS group and 84 in the placebo group. The median baseline VA level among participants was 147.22 (97.20–258.04) ng/ml. There was no significant difference in ICU length of stay between the VAS and placebo groups [14 (7–27) vs. 16.5 (9.3–26) days, P = 0.451]. Similarly, no significant differences were observed between groups regarding hospital length of stay, 28-day mortality, duration of mechanical ventilation, or antibiotic usage. In addition, we performed a post hoc analysis of biomarkers. VAS showed a significant downward trend in lactate levels (P < 0.001), higher 24-h lactate clearance rate (25%), and significantly lower lactate levels on the third day post-intervention (1.28 ± 0.50 vs. 2.20 ± 2.21, P = 0.001). Additionally, VA levels positively correlated with serum albumin (ALB) (r = 0.479, P < 0.001). Procalcitonin (PCT) levels were significantly lower in the VAS group on the 3rd (P = 0.032) and 7th day (P = 0.001) post-intervention, and white blood cell (WBC) count was lower on the 3rd day (P = 0.022). Furthermore, compared with the placebo group, the VAS group had a greater reduction in PCT levels within 24 h following intervention (73% vs. 48%, P = 0.001). No adverse reactions associated with VAS were observed.ConclusionsVAS did not significantly reduce ICU length of stay or 28-day mortality in children with septic shock, however, it may have beneficial effects on systemic inflammation and lactate metabolism. Further studies are warranted to explore the relationship between VA and ALB.Clinical Trial RegistrationClinicaltrials.gov, identifier NCT04127968.